Proceedings of the Eighteenth International Conference on Architectural Support for Programming Languages and Operating Systems 2013
DOI: 10.1145/2451116.2451143
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the dominant out-of-order performance advantage

Abstract: In this paper, we set out to study the performance advantages of an Out-of-Order (OOO) processor relative to in-order processors with similar execution resources. In particular, we try to tease apart the performance contributions from two sources: the improved schedules enabled by OOO hardware speculation support and its ability to generate different schedules on different occurrences of the same instructions based on operand and functional unit availability. We find that the ability to express good static sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In their work, McFarlin et al concluded that the performance advantage of OoO processors against statically scheduled architectures mainly comes from the ability to speculate aggressively [30]. Their experimental study shows that, by replaying dominant schedules as if they were static schedules, the execution can reach 80% of the performance of normal OoO.…”
Section: A Toward Continuous Optimizationsmentioning
confidence: 99%
“…In their work, McFarlin et al concluded that the performance advantage of OoO processors against statically scheduled architectures mainly comes from the ability to speculate aggressively [30]. Their experimental study shows that, by replaying dominant schedules as if they were static schedules, the execution can reach 80% of the performance of normal OoO.…”
Section: A Toward Continuous Optimizationsmentioning
confidence: 99%
“…Although these groups are superficially similar to atomic blocks, they are not saved, specialized, or reused, as our atomic blocks are. Instruction scheduling memoization: McFarlin et al [36] demonstrate that most of out-of-order execution's benefit comes from its ability to use a speculative execution schedule, but not necessarily a different schedule for every instance of an instruction sequence. This is similar to our observation that many static regions of code have stable instruction schedules.…”
Section: Related Workmentioning
confidence: 99%
“…Those less familiar with dynamic scheduling might consult some early descriptions of dynamically scheduled processors [7], [8], more recent designs [9], and a study of the inherent differences between static and dynamic designs [10]. The front end of the core is responsible for fetching, decoding, and enqueuing an instruction for execution, a process which takes several cycles and which here will be referred to as fetch/ decode; see Figure 1.…”
Section: A Dynamically Scheduled Processorsmentioning
confidence: 99%